INSTITUTIONALIZATION OF MODERATE DAKWAH IN MOSQUE MANAGEMENT AT AN-NUR, ROKAN HILIR - Riau Ardana; Soiman (University of Islam Malang, 2025)
This study aims to examine the management strategies of the Mosque Prosperity Board in promoting Dakwah Wasathiyyah (moderate Islamic preaching) at An-Nur Mosque in Bagan Sinembah District, Rokan Hilir Regency. The research focuses on understanding how planning, organizing, mobilizing, and evaluating processes are carried out in alignment with the principles of moderate da'wah. A qualitative approach was employed, with data gathered through observation, interviews, and documentation. The primary source was the chairman of An-Nur Mosque Prosperity Board, supported by secondary sources including journals and mosque congregants. The findings indicate that Mosque Prosperity Board management effectively implements Dakwah Wasathiyyah through strategic planning such as preacher capacity building, thematic study programs, and collaborative outreach. Organizational structure includes specialized teams and advisory councils, while mobilization efforts involve religious moderation training, interfaith dialogue, social activities, and partnerships with external institutions. Annual evaluations ensure the propagation of tolerant, socially just, and harmonious messages. Although the study is limited to one mosque and relies on qualitative insights, it offers a valuable model for applying moderate Islamic principles through institutional mosque management.